The pattern of anxiolytic and hypnotic management by Australian general practice trainees. (18th May 2016) - Holliday, Simon M.; Morgan, Simon; Tapley, Amanda; Henderson, Kim M.; Dunlop, Adrian J.; van Driel, Mieke L.; Spike, Neil A.; McArthur, Lawrence A.; Ball, Jean; Oldmeadow, Christopher J.; Magin, Parker J.
Abstract: Introduction and Aims: Guidelines recommend anxiolytics and hypnotics (A/H) as second‐line, short‐term medications. We aimed to establish prevalence and associations of A/H prescribing by Australian general practice (GP) trainees. Design and Methods: A cross‐sectional analysis from a cohort study of vocational trainees from four GP Regional Training Providers during 2010–2013. General practice trainees act as independent practitioners (including for prescribing purposes) while having recourse to advice from a GP supervisor. Practice and trainee demographic data were collected as well as patient, clinical and educational data from 60 consecutive consultations of each trainee each training term. Analysis was at the level of individual problem managed, with the outcome factor being prescription of any anxiolytic or hypnotic. Results: Overall, 645 registrars (response rate 94.0%) prescribed 68 582 medications in 69 621 consultations (with 112 890 problems managed). A/Hs were prescribed for 1.3% of problems managed and comprised 2.2% of all prescriptions. They were prescribed particularly for insomnia (28.2%) or anxiety (21.8%), but also for many 'off‐label' indications. Significant associations of A/H prescriptions were: patient‐level (greater age, Aboriginal and Torres Strait Islander status, English‐speaking background, being new to the trainee but not to the practice); trainee‐level (male) and consultation‐level (longer duration, pre‐existing problem, specialist referral not being made). Prescribing was significantly lower in one of the four Regional Training Providers. Discussion and Conclusions: GP trainees, inconsistent with most guideline recommendations, prescribe A/Hs mainly as maintenance therapy to unfamiliar and older patients. Our results suggest that changes in management approaches are needed which may be facilitated by support for psychotherapeutic training. [Holliday SM, Morgan S, Tapley A, Henderson KM, Dunlop AJ, van Driel ML, Spike NA, McArthur LA, Ball J, Oldmeadow CJ, Magin PJ. The pattern of anxiolytic and hypnotic management by Australian general practice trainees. Drug Alcohol Rev 2017;36:261-269].